FOOD PRACTICES OF PEOPLE WITH CKD FROM THE PERSPECTIVE OF SUFFERERS AND THEIR CAREGIVERS. A QUALITATIVE STUDY IN MEXICO - Julieta Nataly Peralta Suchil; Luis Eduardo Hernández-Ibarra (Universidade do Estado do Rio de Janeiro, 2016)
Objective: This study aims to determine the dietary practices of people suffering from chronic kidney disease from the perspective of sufferers and their caregivers. Methodology: A qualitative study was conducted with ethnographic approach in San Luis Potosi, Mexico. Focus groups and semi-structured interviews with 16 people with chronic kidney disease and 22 caregivers were performed. The thematic content analysis was performed. Results: The study participants reported having incorporated recommendations regarding the intake of salt, fat and sugar, as well as the amount of drinking water. However, adapting to the family diet prescribed regime and eating out are the main difficulties, especially attending the day of replacement therapies and medical consultations. The use and consumption of homemade or traditional remedies is a common practice among study participants, hoping to improve their health condition. Conclusions: The dietary practices of people with CKD who participated in the study did not match the prescribed dietary recommendations for the treatment of their disease. This may be associated mainly to economic difficulties, beliefs and customs. Further qualitative and participative studies that incorporate practices of the sufferers and their caregivers are needed to better understand the situations that interfere with the ingestion of an adequate diet of those suffering from chronic kidney disease. DOI: 10.12957/demetra.2016.16103